Amamentação em ação: validação de tecnologia assistiva para cegos - Oliveira, Paula Marciana Pinheiro de (2013)
Health promotion also means enabling citizens to act on the determinants of their own health, including disabled people. Hence, health education material accessible to the blind which can be disseminated through the web can enhance their independence and autonomy and are called assistive technology. In this research, the technology “Breastfeeding in action” was used. This technology is cordel literature and, as such, is characterized by the rhyme as a playful strategy. The booklets were selected because of this attribute and breastfeeding because the content is important and because its levels are inferior to the recommendations by competent entities. This theme is experienced by many women and represents a moment of love between mother and child. In addition, breastfed children present less risk of developing illnesses. The aim was to validate assistive technology on breastfeeding in the cordel literature modality in audio through online access for health promotion. A methodological development research was undertaken, using the psychometric model. The research was developed at the Health Communication Laboratory of the Universidade Federal do Ceará. The sample consisted of 124 subjects with a minimum age of 18 years and basic mastery to use the available software. To collect the data, a website was used. The page showed the technology and forms for completion. To analyze the data, means and standard deviations were calculated for the quantitative variables. The qualitative variables were analyzed using the chi-square and likelihood ratio tests. Student’s t-test for independent data or Snedecor’s F-test (ANOVA) were used to compare the means of the topics. Analyses were considered significant when p < 0.05. Approval for the project was obtained from the Research Ethics Committee at Universidade Federal do Ceará. Most subjects were 30-49 years of age (61.3%), female (51.6%), had taken secondary education (48.4%), were not married (55.6%), with an income of up to one minimum wage (2012 - R$ 622.00 / 2013 - R$673.00) (40.3%), who work (75.0%), live in the Northeast (90.3%), are retired (21.8%) and have been blind since birth (51.6%). As regards the assessment of the assistive technology, according to the means found, all topics were favorable, objective (93.6 ± 10.7), organization (87.0 ± 14.5), audio style (86.7 ± 15.6) and motivation (88.9 ± 15.3), and the technology was considered a valid health promotion strategy. The assessment of the technology revealed that it achieved the proposed objectives and intended goals, with a good general organization, structure, presentation strategy and coherence, besides appropriate understanding and a good audio style, able to cause impact, motivation and/or interest. As professionals responsible for health promotion, nurses should increasingly engage in the subjects’ real environment for the sake of a situational diagnosis and consequent effective intervention.